Breast Implant-Associated Anaplastic Large Cell Lymphoma: Case Report and Review of the Literature - Eva Berlin; Kunwar Singh; Christopher Mills; Ilan Shapira; Richard L. Bakst; Manjeet Chadha (Case Reports in Hematology)
We are reporting the case of a 58-year-old woman with history of bilateral silicone breast implants for cosmetic augmentation. At 2-year interval from receiving the breast implants, she presented with swelling of the right breast with associated chest wall mass, effusion around the implant, and axillary lymphadenopathy. Pathology confirmed breast implant-associated anaplastic large cell lymphoma (stage III, T4N2M0, using BIA-ALCL TNM staging and stage IIAE, using Ann-Arbor staging). The patient underwent bilateral capsulectomy and right partial mastectomy with excision of the right breast mass and received adjuvant CHOP chemotherapy and radiation to the right breast and regional nodes. Since completion of multimodality therapy, the patient has sustained remission on both clinical exam and PET/CT scan. We report this case and review of the literature on this rare form of lymphoma.